An adaptive discrete cosine transform coding scheme for digital x-ray images - Mclean, Ivan Hugh (Rhodes University, Faculty of Science, Department of Computer Science, 1989)
The ongoing development of storage devices and technologies for medical image management has led to a growth in the digital archiving of these images. The characteristics of medical x-rays are examined, and a number of digital coding methods are considered. An investigation of several fast cosine transform algorithms is carried out. An adaptive cosine transform coding technique is implemented which produces good quality images using bit rates lower than 0.38 bits per picture element
Keywords: X-rays -- Digitization; Image processing -- Digital techniques; Diagnostic imaging; Computer storage devices